Brief Report: Association of Rheumatoid Factor and Anti-Citrullinated Protein Antibody Positivity With Better Effectiveness of Abatacept: Results From the Pan-European Registry Analysis - Gottenberg, J E; Courvoisier, D S; Hernandez, M V; Iannone, F; Lie, E; Canhão, H; Pavelka, K; Hetland, M L; Turesson, C; Mariette, X; Finckh, A (Arthritis & rheumatology (Hoboken, N.J.), 2016)
OBJECTIVE: To investigate the role of rheumatoid factor (RF) status and anti-citrullinated peptide antibody (ACPA) status as predictors of abatacept (ABA) effectiveness in patients with rheumatoid arthritis (RA). METHODS: We conducted a pooled analysis of data from 9 observational RA registries in Europe (ARTIS [Sweden], ATTRA [Czech Republic], BIOBADASER [Spain], DANBIO [Denmark], GISEA [Italy], NOR-DMARD [Norway], ORA [France], Reuma.pt [Portugal], and SCQM-RA [Switzerland]). Inclusion criteria were a diagnosis of RA, initiation of ABA treatment, and available information on RF and/or ACPA status. The primary end point was continuation of ABA treatment. Secondary end points were ABA discontinuation for ineffectiveness or adverse events and response rates at 1 year (good or moderate response according to the European League Against Rheumatism criteria with LUNDEX adjustment for treatment continuation). Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for the study end points in relation to RF and ACPA status were calculated. RESULTS: We identified 2,942 patients with available data on RA-associated autoantibodies; data on RF status were available for 2,787 patients (77.0% of whom were RF positive), and data on ACPA status were available for 1,903 patients (71.3% of whom were ACPA positive). Even after adjustment for sociodemographic and disease- and treatment-related confounders, RF and ACPA positivity were each associated with a lower risk of ABA discontinuation for any reason (HR 0.79 [95% CI 0.69-0.90], P < 0.001 and HR 0.78 [95% CI 0.68-0.90], P < 0.001, respectively), compared to RF-negative and ACPA-negative patients. Similar associations with RF and ACPA were observed for discontinuation of ABA treatment due to ineffectiveness, with HRs of 0.72 (95% CI 0.61-0.84) and 0.74 (95% CI 0.62-0.88), respectively (both P < 0.001). CONCLUSION: Our results strongly suggest that positivity for RF or ACPA is associated with better effectiveness of ABA therapy.
Keywords: Peptides, Cyclic; revmatoidní faktor; Abatacept; abatacept; Europe; Predictive Value of Tests; výsledek terapie; Evropa; Middle Aged; registrace; mužské pohlaví; Rheumatoid Factor; prediktivní hodnota testů; Registries; ženské pohlaví; Humans; antirevmatika; autoprotilátky; Arthritis, Rheumatoid; lidé středního věku; revmatoidní artritida; Antirheumatic Agents; cyklické peptidy; Female; Treatment Outcome; Autoantibodies; lidé; Male